The mechanical role of the metatarsophalangeal joint in human jumping. - Junichiro Yamauchi; Keiji Koyama (PLoS ONE, 2022)
This study investigated the mechanical role of metatarsophalangeal (MTP) joints in human jumping. Eighteen healthy young men performed three types of single-leg jumps (SJ: squat jump; CMJ: countermovement jump; HJ: standing horizontal jump) on a force plate under barefoot (BARE) and forefoot immobilisation (FFIM) conditions. For FFIM, the forefoot was immobilised around the MTP joints of the dominant leg by a custom-made splint. Force-time components and the centre of pressure (COP) trajectory were measured from the ground reaction force (GRF) in the take-off phase of jumping. The vertical jump heights calculated from the net vertical impulse were lower under FFIM than under BARE during the CMJ (p < 0.05). The HJ distance under FFIM was significantly shorter than that under BARE (p < 0.01). The relative net vertical impulse was lower under FFIM than under BARE during the CMJ (p < 0.05). During the HJ, all the horizontal GRF variables were significantly lower under FFIM than under BARE (p < 0.01), but none of the vertical GRF variables differed between the two conditions. The horizontal relative GRF in the 90-95% of the final take-off phase during the HJ was significantly lower under FFIM than under BARE (p < 0.01). Under FFIM, the COP range in the antero-posterior direction in the take-off phase of the HJ decreased (p < 0.05), whereas its range in the anterior direction for the SJ and CMJ increased (p < 0.05). The results of this study indicate that MTP joint motion can play an important role in regulating force-generating capacities of toe flexor muscles in the take-off phase of human jumping, especially in the horizontal direction of horizontal jumping.